Assessment of agricultural research capacities in Sierra Leone: The case of Sierra Leone Agricultural Research Institute (SLARI) - Momoh, John (International Food Policy Research Institute, 2014)
Given the importance of agriculture in the region, ECOWAS has requested the West and Central African Council for Agricultural Research and Development (CORAF/WECARD) to carry out an in-depth assessment of the critical issues surrounding the human, financial, and institutional capacities in West African agricultural research. Such an assessment is key to the development of national and regional policy recommendations that will ultimately feed into a regional agricultural research strategy for West Africa. To accomplish this assessment, CORAF/WECARD has solicited the support of the Agricultural Science and Technology Indicators (ASTI) program of the International Food Policy Research Institute (IFPRI).